In-Vitro Release Kinetics of Clonazepam from Five Brands of Clonazepam Available in Bangladesh Using UV Spectroscopic Analysis in Deionized Water Media - M. R. Bhuiyan, O. F. Pavel, T. Nandi*, Md. A. Rahman, R. S. Islam Sh. H. Mozumder, K. Sh. Hasan (Journal of Biomedical and Pharmaceutical Research, 2017)
Background and Objective: The purpose of this study was to determine the in vitro release kinetics of five brands of Clonazepam tablets available in the local pharmaceutical market of Bangladesh. Methodology: In this study, five widely prescribed brands C1, C2, C3, C4 and C5 were chosen. All of these brands were 0.5 mg Clonazepam with strip packaging. The dissolution was carried out using USP apparatus-II and the analysis was performed with the UV spectroscopy. To find out the release kinetics, K0 (for zero order), K1 (for first order), Kh (for Higuchi model) were determined. The R2 values for each kinetics were also determined which indicated the linearity of release kinetics for each brand. Result: The study found no brand to follow the zero-order and first order kinetics mostly except Higuchi’s drug release profile. The brands showing different R2 values for Higuchi Drug release profiles are C1 (R2=0.9843), C2 (R2=0.9548), C3 (R2=0.9726), C4 (R2=0.9578), C5 (R2=0.9334) which were the highest amongst the R2 values comparing to zero order and first order values. Conclusion: It is concluded that the available Clonazepam tablet brands available in Bangladesh generally follow the Higuchi’s drug release kinetics. Keywords: Clonazepam, Dissolution, release kinetics, In-vitro drug dissolution, drug release equations.